Am I A Fraud? Occurrence and Factors Associated with Impostor Phenomenon Among Medical Students of Khartoum University, 2022 - Hamad, Hiba K. A. (International Journal of Medical Students, 2025)
Background: The impostor phenomenon (IP) is the tendency to attribute success to external factors rather than to one’s abilities. It is frequent among students and has a negative impact on their wellbeing. This study aimed to assess the occurrence and mental health factors associated with IP in medical students. Methods: Cross-sectional study of University of Khartoum Medical students (December 2021–January 2022), using convenience sampling. We collected the Clance Impostor Phenomenon Scale (CIPS), Patient Health Questionnaire-4 (PHQ-4: anxiety and depression), 2-item Maslach B burnout Inventory (MBI), and Single-Item Self-Esteem Scale (SISE). Data was analyzed using SPSS with correlation analyses, linear regression, and Chi-square tests. Results: Among 409 medical students, the impostor phenomenon (IP) prevalence was 52.8% (216 students), with a mean CIPS score of 63.37 ± 17.02. IP was more common in females (71.8%) and students aged 19–21 years (40.7%). Anxiety (41.6%), depression (48.7%), and burnout (39.6% emotional exhaustion; 26.9% depersonalization) were prevalent, with higher rates in females. Regression analysis showed significant predictors of IP, including burnout (+1.32 points per unit, p < 0.001), perfectionism (+0.86 points per unit, p < 0.001), parental overprotection (+2.43 points per unit, p < 0.001), and depression (+2.90 points, p = 0.024), while self-esteem showed a negative association (−4.19 points per unit, p < 0.001). Gender differences were observed in three CIPS items, with stronger female endorsements. Conclusions: IP is prevalent and linked to family dynamics, personality traits, and mental health issues. Efforts to increase awareness and facilitate IP management should be implemented.